Cytogenetic and molecular characterization of two isodicentric Y chromosomes - Stankiewicz, Paweł; Hélias‐Rodzewicz, Zofia; Jakubów‐Durska, Krystyna; Bocian, Ewa; Obersztyn, Ewa; Rappold, Gudrun; Mazurczak, Tadeusz (American journal of medical genetics, 2001)
We report the results of detailed molecular-cytogenetic studies of two isodicentric Y [idic(Y)] chromosomes identified in patients with complex mosaic karyotypes. We used fluorescence in situ hybridization (FISH) and polymerase chain reaction (PCR) to determine the structure and genetic content of the abnormal chromosomes. In the first patient, classical cytogenetics and FISH analysis with Y chromosome-specific probes showed in peripheral blood lymphocytes a karyotype with 4 cell lines: 45,X[128]/46,X,+idic(Y)(p11.32)[65]/47,XY,+idic(Y)(p11.32)[2]/47,X,+2idic(Y)(p11.32)[1]. No Y chromosome material was found in the removed gonads. For precise characterization of the Yp breakpoint, FISH and fiberFISH analysis, using a telomeric probe and a panel of cosmid probes from the pseudoautosomal region PAR1, was performed. The results showed that the breakpoint maps ∼1,000 Kb from Ypter. The second idic(Y) chromosome was found in a boy with mild mental retardation, craniofacial anomalies, and the karyotype in lymphocytes 47,X,+idic(Y)(q11.23),+i(Y)(p10)[77]/46,X,+i(Y)(p10)[23]. To our knowledge, such an association has not been previously described. FISH and PCR analysis indicated the presence of at least two copies of the SRY gene in all analyzed cells. Using 17 PCR primers, the Yq breakpoint was shown to map between sY123 (DYS214) and sY121 (DYS212) loci in interval 5O in AZFb region. Possible mechanisms of formation of abnormal Y chromosomes and karyotype-phenotype correlations are discussed. © 2001 Wiley-Liss, Inc.